Composite positive plate, diaphragm-free lithium battery and lithium battery
By introducing a composite structure loading oxygen trapping agent in the molecular sieve into the positive electrode sheet of the lithium battery and introducing a functional layer on the surface, the problem of oxygen gas released by the positive electrode of the lithium battery is solved, and the safety performance of the battery is significantly improved.
Patent Information
- Application Number
- CN202411121543.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-15
- Publication Date
- 2025-05-02
AI Technical Summary
The positive electrode material in lithium batteries releases reactive oxygen and combustible gases during the circulation process, resulting in a degradation of battery safety performance.
A composite positive electrode sheet is adopted, which includes a composite structure uniformly distributed within the positive electrode active material, a composite structure formed by loading an oxygen capture agent in the molecular sieve, and a surface functional layer is introduced on the surface of the positive electrode sheet layer to capture oxygen and isolate the positive and negative electrode sheets.
Effectively capture the reactive oxygen produced by the positive electrode, reduce the battery's self-exothermic reaction, reduce the probability of thermal runaway, and improve the safety performance of lithium batteries.
Abstract
Description
Technical Field
[0001] The present invention relates to a composite positive electrode sheet, a lithium battery without a diaphragm and a lithium battery, belonging to the field of batteries. More specifically, the present invention relates to a composite positive electrode sheet and corresponding lithium batteries without a diaphragm and with a diaphragm. Background Art
[0002] In actual use, lithium batteries need to have not only excellent electrochemical properties but also good safety performance. With the development of high-energy lithium batteries, positive electrode materials are developing towards high nickel / ultra-high nickel, but high nickel / ultra-high nickel materials show poor safety performance in batteries. Part of the reason for the poor safety performance is that during the cycle, the distortion of the lattice structure of the positive electrode active material releases active oxygen, triggering adverse chemical reactions and uncontrollable heat release inside the battery; at the same time, the reduction reaction on the negative electrode side surface will produce flammable gases such as methane and ethylene. Although the diaphragm-free battery has improved the safety of lithium-ion batteries to a certain extent by using solid electrolytes to replace the diaphragms in traditional lithium-ion batteries to prevent the safety hazards caused by the shrinkage of the diaphragm at high temperatures, the above-mentioned problem of positive electrode releasing oxygen and causing uncontrollable heat release still exists.
[0003] It is desirable to seek a technical solution for improving the safety performance of the battery without compromising the electrochemical performance of the lithium battery and the separator-free lithium battery, so as to overcome the deficiencies in the prior art. Summary of the invention
[0004] Problem that the invention aims to solve
[0005] Because the positive electrode materials used in lithium batteries produce gases under chemical or electrochemical conditions inside the battery under normal cycles and abuse, especially active oxygen and flammable gases released by the positive electrode, the battery safety performance deteriorates.
[0006] In order to improve the safety issues caused by active oxygen crosstalk at the positive electrode, the present invention aims to provide a technical solution for improving the safety performance of lithium batteries with and without separators.
[0007] Solutions for solving problems
[0008] In view of such circumstances, the present inventors have diligently studied and provided the following embodiments.
[0009] One aspect of the present invention provides a composite positive electrode sheet, which comprises at least a positive electrode sheet layer,
[0010] The positive electrode layer includes a composite structure uniformly distributed in the positive electrode active material.
[0011] The composite structure is formed by loading molecules of an oxygen capture agent, which is liquid at room temperature, within the molecular sieve.
[0012] Furthermore, according to the above composite positive electrode sheet, the composite structure accounts for 0.5% to 5% of the mass of the positive electrode active material in the composite positive electrode sheet.
[0013] Another aspect of the present invention provides a composite positive electrode sheet, which comprises at least a positive electrode sheet layer and a surface functional layer on the outermost surface of the positive electrode sheet layer.
[0014] Wherein, the surface functional layer at least includes a composite structure,
[0015] The composite structure is formed by loading molecules of an oxygen capture agent, which is liquid at room temperature, within the molecular sieve.
[0016] Furthermore, according to the above composite positive electrode sheet, the composite structure accounts for 0.5% to 5% of the mass of the positive electrode active material in the composite positive electrode sheet.
[0017] Furthermore, according to the above-mentioned composite positive electrode sheet, the thickness of the surface functional layer is 0.5 to 10 μm, preferably 1 to 5 μm, and the porosity of the surface functional layer is 10% to 40%.
[0018] In addition, according to the above-mentioned composite positive electrode sheet, the mass ratio of the oxygen capture agent to the molecular sieve is oxygen capture agent: molecular sieve = 1:30 to 1:1, preferably oxygen capture agent: molecular sieve = 1:9 to 1:1.5.
[0019] In the present invention, according to the above-mentioned composite positive electrode sheet, the oxygen capture agent is selected from fluorine-containing carbon compounds, preferably at least one selected from perfluoro-n-butyltetrahydrofuran, perfluoro tertiary amine compounds, Freon E4, and perfluorodecalin compounds.
[0020] In the present invention, according to the above-mentioned composite positive electrode sheet, the molecular sieve is at least one selected from carbon molecular sieve, titanium silicon molecular sieve, silicon aluminum molecular sieve, and phosphorus aluminum molecular sieve, preferably at least one selected from CMS220 carbon molecular sieve, TS-1 titanium silicon molecular sieve, 3A molecular sieve silicon aluminum, and SAPO34 phosphorus aluminum molecular sieve.
[0021] In the present invention, according to the above-mentioned composite positive electrode sheet, the pore size of the molecular sieve is 0.2nm to 2nm.
[0022] In the present invention, according to the above composite positive electrode sheet, the content of the molecular sieve is 40% to 90% relative to the total mass of the composite structure.
[0023] In the present invention, according to the above-mentioned composite positive electrode sheet, the surface functional layer further comprises a binder, and the binder is at least one selected from polyacrylate, polyvinylidene fluoride and its derivatives, polyether, polyurethane, and polyamide.
[0024] In the present invention, according to the above-mentioned composite positive electrode sheet, the composite positive electrode sheet further comprises a solid electrolyte layer, and the solid electrolyte layer comprises an inorganic, organic or composite solid electrolyte.
[0025] The inorganic solid electrolyte is at least one selected from oxide solid electrolytes, halide solid electrolytes, and sulfide solid electrolytes; the organic solid electrolyte is at least one selected from polyvinylidene fluoride (PVDF), polyacrylonitrile (PAN), and polyacrylate; and the composite solid electrolyte is a composite structure of the inorganic solid electrolyte and the organic solid electrolyte.
[0026] Another aspect of the present invention provides a method for preparing the above-mentioned composite positive electrode sheet, wherein the composite positive electrode sheet at least comprises a positive electrode sheet layer and a composite structure uniformly distributed in the positive electrode sheet layer.
[0027] The preparation method comprises the step of mixing the molecular sieve and the oxygen capture agent to form a composite structure.
[0028] In the preparation method of the present invention, the preparation method comprises the step of uniformly mixing the composite structure with a positive electrode active material, a conductive agent, a binder and a solvent to prepare a positive electrode slurry.
[0029] Another aspect of the present invention provides a method for preparing the above-mentioned composite positive electrode sheet, wherein the composite positive electrode sheet at least comprises a positive electrode sheet layer and a surface functional layer on the surface of the positive electrode sheet layer, wherein the surface functional layer comprises a composite structure,
[0030] The preparation method comprises the step of mixing the molecular sieve and the oxygen capture agent to form a composite structure.
[0031] In the preparation method of the present invention, the preparation method comprises the step of coating the composite structure on the surface of the positive electrode layer to form the surface functional layer.
[0032] In the preparation method of the present invention, the preparation method further comprises the step of using an inorganic, organic or composite solid electrolyte to form a solid electrolyte layer in the composite positive electrode sheet.
[0033] Another aspect of the present invention provides a diaphragm-free lithium battery, which at least includes the composite positive electrode sheet according to the above-mentioned composite positive electrode sheet or the composite positive electrode sheet obtained by the above-mentioned preparation method, and a composite negative electrode sheet.
[0034] Another aspect of the present invention provides a lithium battery, which at least includes the composite positive electrode sheet according to the above-mentioned composite positive electrode sheet or the composite positive electrode sheet obtained by the above-mentioned preparation method, and a composite negative electrode sheet.
[0035] Further, according to the above lithium battery, wherein the composite negative electrode sheet at least comprises a negative electrode sheet layer, and optionally a solid electrolyte layer on the outermost surface of the negative electrode sheet layer,
[0036] The negative electrode layer at least includes a negative electrode active material, a conductive agent and a binder, and the negative electrode active material is at least one selected from lithium metal, graphite or silicon-based negative electrode active materials.
[0037] Furthermore, according to the above lithium battery, the negative electrode layer further comprises a porous material, the pore size of the porous material is 0.3 nm to 1 nm, preferably 5A zeolite,
[0038] The content of the porous material is 0.1% to 5% relative to the total mass of the negative electrode layer.
[0039] In addition, according to the above lithium battery, the thickness of the solid electrolyte layer is 5 μm to 20 μm, and the porosity is 5% to 30%.
[0040] The solid electrolyte layer comprises an inorganic, organic or composite solid electrolyte,
[0041] The inorganic solid electrolyte is at least one selected from oxide solid electrolytes, halide solid electrolytes, and sulfide solid electrolytes; the organic solid electrolyte is at least one selected from polyvinylidene fluoride (PVDF), polyacrylonitrile (PAN), and polyacrylate; and the composite solid electrolyte is a composite electrolyte of the inorganic solid electrolyte and the organic solid electrolyte.
[0042] Effects of the Invention
[0043] In the present invention, a composite molecular sieve with high oxygen capture / adsorption capacity is used to uniformly disperse it inside the composite positive electrode sheet, thereby capturing the active oxygen components generated by the positive electrode. Furthermore, when a functional layer of a certain thickness is introduced on the surface of the positive electrode sheet, it can simultaneously capture oxygen and isolate the positive and negative electrode sheets to prevent short circuits. Therefore, the use of a composite molecular sieve with high oxygen capture / adsorption capacity can provide further protection for the preparation of diaphragm-free lithium batteries. On the other hand, a porous material with high adsorption capacity for methane, ethylene, etc. is used on the negative electrode side of the battery to reduce the probability of gas migration to the positive electrode.
[0044] By adopting the above technical solution, the self-heating reaction caused by the oxidizing gas and reducing gas generated in the lithium battery can be delayed, reducing the self-heating temperature rise of the battery under abuse conditions, reducing the heat release, and reducing the probability of thermal runaway. DETAILED DESCRIPTION
[0045] Various exemplary embodiments, features and aspects of the present invention will be described in detail below. The word "exemplary" used here means "used as an example, embodiment or illustrative". Any embodiment described here as "exemplary" is not necessarily interpreted as being superior or better than other embodiments.
[0046] In addition, in order to better illustrate the present invention, numerous specific details are provided in the following specific embodiments. It should be understood by those skilled in the art that the present invention can be implemented without certain specific details. In other examples, methods, means, equipment and steps well known to those skilled in the art are not described in detail in order to highlight the subject matter of the present invention.
[0047] Unless otherwise stated, the units used in this specification are all international standard units, and the numerical values and numerical ranges appearing in the present invention should be understood to include the inevitable systematic errors in industrial production.
[0048] In this specification, the word "may" includes both performing a certain process and not performing a certain process.
[0049] In this specification, the references to "some specific / preferred embodiments", "other specific / preferred embodiments", "embodiments", etc., mean that the specific elements (e.g., features, structures, properties and / or characteristics) described in connection with the embodiments are included in at least one embodiment described herein, and may or may not exist in other embodiments. In addition, it should be understood that the elements may be combined in various embodiments in any suitable manner.
[0050] In this specification, the numerical range expressed using "a numerical value A to a numerical value B" means a range including the endpoints A and B.
[0051] In this specification, "room temperature" means a temperature within a range of 10°C to 30°C.
[0052] <First aspect>
[0053] The composite positive electrode sheet provided by the first aspect of the present invention comprises at least a positive electrode sheet layer, the positive electrode sheet layer comprises a composite structure uniformly distributed in the positive electrode active material, the composite structure is formed by loading molecules of an oxygen capture agent in a molecular sieve, and the oxygen capture agent is liquid at room temperature. Alternatively, a composite positive electrode sheet provided by the first aspect of the present invention comprises at least a positive electrode sheet layer and a surface functional layer on the outermost surface of the positive electrode sheet layer, the surface functional layer comprises at least a composite structure, the composite structure is formed by loading molecules of an oxygen capture agent in a molecular sieve, and the oxygen capture agent is liquid at room temperature.
[0054] In a specific embodiment of the present invention, the above-mentioned composite structure is 0.5% to 5% of the mass of the positive electrode active material in the composite positive electrode sheet. In a specific embodiment, the oxygen capture agent in the above-mentioned composite structure can be evenly dispersed and fixed in the pores of the molecular sieve. The oxygen capture agent is filled in the pores of the molecular sieve by impregnation-centrifugation, and the oxygen capture agent after drying is fixed in the pores of the molecular sieve. In a specific embodiment, the impregnation method is: add the molecular sieve and the oxygen capture agent to the reaction vessel, evacuate to -90kPa, maintain the vacuum for 5 minutes and then release the pressure, and continuously perform the vacuum-pressure release cycle 3 times, and the temperature is controlled between 25°C and 50°C. After doing this, the oxygen capture agent as a liquid penetrates into the pores of the molecular sieve, and the molecules of the oxygen capture agent fixed in the pores of the molecular sieve exist in a non-flowing state. In addition, the molecular sieve itself can also capture a certain amount of oxygen, so the composite structure of the present invention can achieve more oxygen adsorption.
[0055] In a specific embodiment of the present invention, the mass ratio of oxygen capture agent to molecular sieve is oxygen capture agent: molecular sieve = 1:30 to 1:1, preferably oxygen capture agent: molecular sieve = 1:9 to 1:1.5. By making the mass ratio of oxygen capture agent to molecular sieve between 1:30 and 1:1, preferably 1:9 to 1:1.5, the surface functional layer stacked on the outermost surface of the positive electrode layer does not affect the deintercalation and transfer of lithium ions, thereby ensuring the smooth progress of the electrochemical reaction. In addition, the mass ratio of oxygen capture agent to molecular sieve within the above range will not endanger the structure and strength of the composite positive electrode sheet, etc., and can enable the composite positive electrode sheet to fully maintain its function under normal circulation and abuse conditions, thereby ensuring the safety of the battery.
[0056] In a specific embodiment of the present invention, in addition to the composite structure formed by the molecules of the oxygen capture agent loaded in the molecular sieve included in the surface functional layer, the composite structure can also be introduced into the positive electrode layer. That is, the positive electrode layer can also include a composite structure formed by the molecules of the oxygen capture agent loaded in the molecular sieve distributed in the positive electrode active material. In this case, the mass of the composite structure relative to the positive electrode active material in the composite positive electrode sheet can also be 0.5% to 5%.
[0057] In a specific embodiment of the present invention, the positive electrode active material comprises at least one selected from lithium iron phosphate (LFP), lithium iron manganese phosphate (LMFP), lithium nickel manganese oxide (LiNMO), lithium manganese oxide (LMO), lithium cobalt oxide (LCO), ternary materials such as lithium nickel cobalt manganese oxide (NCM) or lithium nickel cobalt aluminum oxide (NCA), etc. In the composite structure, the mass ratio of oxygen capture agent to molecular sieve is oxygen capture agent: molecular sieve = 1:30 to 1:1, preferably oxygen capture agent: molecular sieve = 1:9 to 1:1.5.
[0058] In addition, the introduction of a composite structure into the positive electrode layer can capture oxygen at the first time when the positive electrode active material releases oxygen, and in the presence of a surface functional layer, it works together with the surface functional layer to further reduce the diffusion of oxygen to the negative electrode side.
[0059] In a preferred embodiment, the thickness of the surface functional layer is 0.5 to 10 μm, preferably 1 to 5 μm. The porosity of the surface functional layer is 10% to 40%. By introducing a surface functional layer of a certain thickness on the surface of the positive electrode layer, it can simultaneously capture oxygen and isolate the positive and negative electrodes to prevent short circuits, thereby providing further protection for the preparation of diaphragm-free lithium batteries. The thickness of the functional layer (between 0.5 and 10 μm) is controlled by adjusting the concentration of the coating dispersion of the surface functional layer (the mass concentration of the molecular sieve is 5% to 40%) and the thickness of the liquid layer before drying (between 1 and 30 μm). Further, the porosity is adjusted by changing the solid content of the coating dispersion (between 8% and 50%).
[0060] In a preferred embodiment, the oxygen capture agent is selected from fluorine-containing carbon compounds, preferably at least one selected from perfluoro-n-butyltetrahydrofuran, perfluoro tertiary amine compounds (such as perfluorotripropylamine), Freon E4, and perfluorodecalin (such as perfluoro(decalin)). The oxygen capture agent can effectively absorb the active oxygen released by the positive electrode, block the self-exothermic reaction caused by the oxidizing gas and reducing gas generated in the lithium battery, and reduce the probability of thermal runaway. In this way, the aggravation of thermal runaway of the battery due to the presence of active oxygen inside the battery can be avoided, and the risk of battery fire can be reduced.
[0061] In a preferred embodiment, the molecular sieve is at least one selected from carbon molecular sieve, titanium silicon molecular sieve, silicon aluminum molecular sieve, phosphorus aluminum molecular sieve, preferably at least one selected from CMS220 carbon molecular sieve, TS-1 titanium silicon molecular sieve, 3A molecular sieve silicon aluminum, SAPO34 phosphorus aluminum molecular sieve. The molecular sieve has many channels and holes in structure, a large specific surface area, and a strong ability to adsorb gas molecules and electrolyte molecules. On the other hand, the molecular sieve has polarity and can also adsorb molecules containing polar groups.
[0062] In a preferred embodiment, the pore size of the molecular sieve is 0.2 nm to 2 nm. The content of the molecular sieve is 40% to 90% relative to the total mass of the composite structure. By controlling the pore size and content of the molecular sieve, the active oxygen released by the positive electrode is fully absorbed, and the transfer of lithium ions from the positive electrode to the negative electrode is not hindered, and the battery performance is not affected.
[0063] In a preferred embodiment, the surface functional layer further comprises a binder. The binder is at least one selected from polyacrylate, polyvinylidene fluoride and its derivatives, polyether, polyurethane, and polyamide. By using a binder in the surface functional layer, the surface functional layer and the positive electrode layer in the composite positive electrode sheet can be firmly bonded, and the surface functional layer can also be prevented from structural collapse due to wetting by electrolyte or the like during use.
[0064] In a specific embodiment of the present invention, the composite positive electrode sheet also includes a solid electrolyte layer. In the case where the composite positive electrode sheet does not include a surface functional layer, the solid electrolyte layer is located above the positive electrode sheet layer; and in the case where the surface functional layer is included, the solid electrolyte layer is located above the surface functional layer. The solid electrolyte layer comprises an inorganic, organic or composite solid electrolyte. There is no particular restriction on the solid electrolyte, and it can be appropriately selected as needed. The inorganic solid electrolyte is at least one selected from an oxide solid electrolyte, a halide solid electrolyte, and a sulfide solid electrolyte, including but not limited to oxide solid electrolytes such as LLZO, LATP, and LLZTO, halide solid electrolytes such as Li3YBr6, Li3InCl6, and sulfide solid electrolytes such as LPS and LGPS. The organic solid electrolyte is at least one selected from polyvinylidene fluoride (PVDF), polyacrylonitrile (PAN), and polyacrylate. The composite solid electrolyte is a composite structure of an inorganic solid electrolyte and an organic solid electrolyte.
[0065] In a further embodiment, the solid electrolyte layer contains a binder. There is no particular limitation on the binder, and it may include polyacrylates, polyvinylidene fluoride and derivatives, polyethers, polyurethanes, and polyamides. In addition, a binder that is the same as or different from the binder selected in the surface functional layer may be used. In a preferred embodiment, the same binder is used in the solid electrolyte layer and the surface functional layer.
[0066] <Second Aspect>
[0067] The third aspect of the present invention provides a method for preparing the above-mentioned composite positive electrode sheet, the preparation method comprising the step of mixing a molecular sieve with an oxygen capture agent to form a composite structure. Further, the preparation method of the present invention also comprises the step of using an inorganic, organic or composite solid electrolyte to form a solid electrolyte layer in the composite positive electrode sheet.
[0068] In one embodiment, the step of mixing the molecular sieve and the oxygen capture agent to form a composite structure is performed by an impregnation method, wherein the molecular sieve and the oxygen capture agent are added to a reaction vessel, evacuated to -90 kPa, maintained in vacuum for 5 minutes and then released, and the vacuum-release cycle is performed continuously for 3 times, and the temperature is controlled between 25° C. and 50° C. In this way, the composite structure of the present invention can be easily and quickly formed.
[0069] In a specific embodiment of the present invention, the composite positive electrode sheet according to the present invention comprises at least a positive electrode sheet layer and a composite structure uniformly distributed in the positive electrode sheet layer, and the preparation method of the present invention comprises the step of uniformly mixing the composite structure with a positive electrode active material, a conductive agent, a binder and a solvent to prepare a positive electrode slurry. The proportion of the raw materials of the positive electrode slurry can be adjusted as needed to obtain a viscosity suitable for coating.
[0070] In a specific embodiment of the present invention, the composite positive electrode sheet according to the present invention comprises at least a positive electrode sheet layer and a surface functional layer on the surface of the positive electrode sheet layer, the surface functional layer comprises a composite structure, and the preparation method of the present invention comprises the step of coating the composite structure on the surface of the positive electrode sheet layer to form the surface functional layer. The viscosity of the composite structure can be adjusted as needed to be suitable for coating.
[0071] In a specific embodiment of the present invention, the obtained composite positive electrode sheet can be dried, compacted, striped, and the tabs are welded and encapsulated, and then used in the manufacture of lithium-ion batteries.
[0072] <Third Aspect>
[0073] The third aspect of the present invention provides a lithium battery and a separator-free lithium battery, which at least include the composite positive electrode sheet according to the present invention or the composite positive electrode sheet obtained by the preparation method of the present invention, and a composite negative electrode sheet.
[0074] In a specific embodiment of the present invention, the lithium battery is a lithium battery without a diaphragm and a lithium battery with a diaphragm. Specifically, the lithium battery can be formed by combining a composite positive electrode sheet with a common negative electrode sheet, a composite positive electrode sheet with a composite negative electrode sheet, or a common positive electrode sheet with a composite negative electrode sheet, without a diaphragm. In addition, the lithium battery can be formed by combining a composite positive electrode sheet with a common negative electrode sheet and a diaphragm, a composite positive electrode sheet with a composite negative electrode sheet and a diaphragm, or a common positive electrode sheet with a composite negative electrode sheet and a diaphragm, and contains a diaphragm.
[0075] In a specific embodiment of the present invention, the composite negative electrode sheet includes at least a negative electrode sheet layer, and optionally a solid electrolyte layer on the outermost surface of the negative electrode sheet layer. The negative electrode sheet layer includes at least a negative electrode active material, a conductive agent and a binder. There is no particular limitation on the negative electrode active material, and the negative electrode active material can be at least one selected from lithium metal, graphite or silicon-based negative electrode active materials. In addition, the conductive agent and the binder can be selected from those commonly used in the art.
[0076] In an exemplary embodiment, the negative electrode layer further includes a porous material. The pore size of the porous material is 0.3 nm to 1 nm, preferably 5A zeolite, wherein the content of the porous material is 0.1% to 5% relative to the total mass of the negative electrode layer. The porous material does not hinder ion permeation, does not affect the composite negative electrode sheet to perform its function, and thus does not affect the battery performance.
[0077] In addition, porous materials have high adsorption capacity for methane, ethylene, etc. Using the above porous materials on the negative electrode side of the battery reduces the probability of gas migration to the positive electrode, thereby blocking the redox reaction caused by the gas generated by the positive and negative electrodes, preventing self-heating, and thus inhibiting the self-heating temperature increase of the battery under abuse.
[0078] In an exemplary embodiment, the thickness of the solid electrolyte layer on the outermost surface of the negative electrode layer is 5 μm to 20 μm, and the porosity is 5% to 30%. The thickness is controlled by adjusting the concentration of the coating dispersion of the solid electrolyte layer (the mass concentration of the solid electrolyte is 8% to 45%) and the thickness of the liquid layer before drying (between 10 μm and 50 μm). Further, the porosity is adjusted by changing the solid content of the coating dispersion (between 10% and 50%).
[0079] As described above, in an exemplary embodiment, the solid electrolyte layer includes an inorganic, organic or composite solid electrolyte. The solid electrolyte is not particularly limited and can be appropriately selected as needed.
[0080] The inorganic solid electrolyte is at least one selected from oxide solid electrolytes, halide solid electrolytes, and sulfide solid electrolytes, including but not limited to oxide solid electrolytes such as LLZO, LATP, and LLZTO, halide solid electrolytes such as Li3YBr6 and Li3InCl6, and sulfide solid electrolytes such as LPS and LGPS. The organic solid electrolyte is at least one selected from polyvinylidene fluoride (PVDF), polyacrylonitrile (PAN), and polyacrylate. The composite solid electrolyte is a composite structure of the inorganic solid electrolyte and the organic solid electrolyte.
[0081] In a specific embodiment of the present invention, a lithium battery is provided, which includes a composite positive electrode sheet and a composite negative electrode sheet. The composite positive electrode sheet includes a positive electrode sheet layer and a surface functional layer. Among them, the positive electrode sheet layer at least includes a positive electrode active material, a conductive agent, and a binder, and a composite structure formed by an oxygen capture agent and a molecular sieve can also be added. The surface functional layer at least includes a composite structure formed by an oxygen capture agent and a molecular sieve, and the composite structure includes an oxygen capture agent, a molecular sieve, and a binder. The binder includes polyacrylates, polyvinylidene fluoride and derivatives, polyethers, polyurethanes, and polyamides; an inorganic, organic or composite solid electrolyte layer can also be added. The solid electrolyte layer contains a binder, and the binder is the same as the binder in the composite structure.
[0082] Example
[0083] The embodiments of the present invention will be described in detail below in conjunction with the examples, but those skilled in the art will appreciate that the following examples are only used to illustrate the present invention and should not be considered to limit the scope of the present invention. If no specific conditions are specified in the examples, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be obtained commercially.
[0084] Example 1
[0085] The mass ratio of the positive electrode layer is NCM811:SP:PVDF:CNT=96:1.5:2:0.5. The above raw materials are mixed and coated to obtain a positive electrode layer. Perfluorobutyltetrahydrofuran:CMS carbon molecular sieve=1:3 (mass ratio), mixed and evenly coated on the surface of the positive electrode layer, with a thickness of 3μm and a porosity of 25%. The mass ratio of the composite structure formed by perfluorobutyltetrahydrofuran and CMS carbon molecular sieve to the positive electrode active material in the composite positive electrode sheet is 1%. Thus, the composite positive electrode sheet A of Example 1 is obtained, and the composite positive electrode sheet A includes a surface functional layer containing a composite structure on the outermost surface of the positive electrode layer.
[0086] The negative electrode sheet is a graphite negative electrode, and the mass ratio of each component of the negative electrode is graphite: SP: CNT: CMC: SBR = 94: 1.5: 0.5: 1.5: 2.5. The raw materials are mixed and coated to obtain a negative electrode sheet.
[0087] Example 2
[0088] The mass ratio of the positive electrode layer is NCM811:SP:PVDF:CNT=96:1.5:2:0.5. Perfluoro-n-butyltetrahydrofuran:CMS carbon molecular sieve=1:3 (mass ratio), mixed evenly and used for the preparation of the positive electrode layer. Next, the above mixture is mixed with the raw material mixture of the positive electrode layer, so that the composite structure formed by perfluoro-n-butyltetrahydrofuran and CMS carbon molecular sieve is evenly distributed in the positive electrode layer. The mixture thus obtained is coated to obtain a positive electrode sheet. The mass ratio of the composite structure formed by perfluoro-n-butyltetrahydrofuran and CMS carbon molecular sieve to the positive electrode active material in the composite positive electrode sheet is 1%, which is evenly distributed in the positive electrode layer. Thus, the composite positive electrode sheet B of Example 2 is obtained, and the composite positive electrode sheet B includes a composite structure evenly distributed in the positive electrode active material in the positive electrode layer.
[0089] The negative electrode sheet is a graphite negative electrode, and the mass ratio of each component of the negative electrode is graphite: SP: CNT: CMC: SBR = 94: 1.5: 0.5: 1.5: 2.5. The raw materials are mixed and coated to obtain a negative electrode sheet.
[0090] Example 3
[0091] The mass ratio of the positive electrode layer is NCM811:SP:PVDF:CNT=96:1.5:2:0.5. Perfluoro-n-butyltetrahydrofuran:CMS carbon molecular sieve=1:3 (mass ratio), which is used for the preparation of the positive electrode layer after being evenly mixed. Next, the above mixture is mixed with the raw material mixture of the positive electrode layer, so that the composite structure formed by perfluoro-n-butyltetrahydrofuran and CMS carbon molecular sieve is evenly distributed in the positive electrode layer. The mixture thus obtained is coated to obtain a positive electrode sheet. As a result, the mass ratio of the composite structure formed by perfluoro-n-butyltetrahydrofuran and CMS carbon molecular sieve to the positive electrode active material in the composite positive electrode sheet is 1%, which is evenly distributed in the positive electrode sheet.
[0092] In addition, perfluoro-n-butyltetrahydrofuran: CMS carbon molecular sieve = 1:3 (mass ratio), mixed and evenly coated on the surface of the positive electrode layer, with a thickness of 3 μm and a porosity of 25%. The mass ratio of the composite structure formed by perfluoro-n-butyltetrahydrofuran and CMS carbon molecular sieve to the positive electrode active material in the composite positive electrode sheet is 2%. Thus, the composite positive electrode sheet C of Example 3 is obtained, and the composite positive electrode sheet C includes a composite structure uniformly distributed in the positive electrode active material in the positive electrode sheet layer and a surface functional layer containing the composite structure on the outermost surface of the positive electrode sheet layer.
[0093] The negative electrode sheet is a graphite negative electrode, and the mass ratio of each component of the negative electrode is graphite: SP: CNT: CMC: SBR = 94: 1.5: 0.5: 1.5: 2.5. The raw materials are mixed and coated to obtain a negative electrode sheet.
[0094] Example 4
[0095] The mass ratio of the positive electrode layer is NCM811:SP:PVDF:CNT=96:1.5:2:0.5. The above raw materials are mixed and coated to obtain a positive electrode layer. Perfluorobutyltetrahydrofuran: SAPO34 molecular sieve=1:4 (mass ratio), mixed and evenly coated on the surface of the positive electrode layer, with a thickness of 2μm and a porosity of 30%. The mass ratio of the composite structure formed by perfluorobutyltetrahydrofuran and SAPO34 molecular sieve to the positive electrode active material in the composite positive electrode sheet is 2%. Thus, the composite positive electrode sheet D of Example 4 is obtained, and the composite positive electrode sheet D includes a surface functional layer containing a composite structure on the outermost surface of the positive electrode layer.
[0096] The negative electrode sheet is a graphite negative electrode, and the mass ratio of each component of the negative electrode is graphite: SP: CNT: CMC: SBR = 94: 1.5: 0.5: 1.5: 2.5. The raw materials are mixed and coated to obtain a negative electrode sheet.
[0097] Comparative Example 1
[0098] The mass ratio of the positive electrode sheet is NCM811:SP:PVDF:CNT=96:1.5:2:0.5. The raw materials are mixed and coated to obtain the positive electrode sheet.
[0099] The negative electrode sheet is a graphite negative electrode, and the mass ratio of each component of the negative electrode is graphite: SP: CNT: CMC: SBR = 94: 1.5: 0.5: 1.5: 2.5. The raw materials are mixed and coated to obtain a negative electrode sheet.
[0100] Comparative Example 2
[0101] The mass ratio of the positive electrode layer is NCM811:SP:PVDF:CNT=96:1.5:2:0.5. Perfluoro-n-butyltetrahydrofuran:CMS carbon molecular sieve=1:50 (mass ratio), mixed evenly and used for the preparation of the positive electrode layer. Next, the above mixture is mixed with the raw material mixture of the positive electrode layer, so that the composite structure formed by perfluoro-n-butyltetrahydrofuran and CMS carbon molecular sieve is evenly distributed in the positive electrode layer. The mixture thus obtained is coated to obtain a positive electrode sheet. As a result, the mass ratio of the composite structure formed by perfluoro-n-butyltetrahydrofuran and CMS carbon molecular sieve to the positive electrode active material in the composite positive electrode sheet is 0.01%, which is evenly distributed in the positive electrode layer. The composite positive electrode sheet E of Comparative Example 2 is obtained, and the composite positive electrode sheet E includes a composite structure evenly distributed in the positive electrode active material in the positive electrode layer.
[0102] The negative electrode sheet is a graphite negative electrode, and the mass ratio of each component of the negative electrode is graphite: SP: CNT: CMC: SBR = 94: 1.5: 0.5: 1.5: 2.5. The raw materials are mixed and coated to obtain a negative electrode sheet.
[0103] Comparative Example 3
[0104] The mass ratio of the positive electrode layer is NCM811:SP:PVDF:CNT=96:1.5:2:0.5. The above raw materials are mixed and coated to obtain a positive electrode layer. Perfluorobutyltetrahydrofuran:CMS carbon molecular sieve=1:50 (mass ratio), mixed and evenly coated on the surface of the positive electrode layer, with a thickness of 0.5μm and a porosity of 25%. The mass ratio of the composite structure formed by perfluorobutyltetrahydrofuran and CMS carbon molecular sieve to the positive electrode active material in the composite positive electrode sheet is 0.01%. Thus, the composite positive electrode sheet F of Comparative Example 3 is obtained, and the composite positive electrode sheet F includes a surface functional layer containing a composite structure on the outermost surface of the positive electrode layer.
[0105] The negative electrode sheet is a graphite negative electrode, and the mass ratio of each component of the negative electrode is graphite: SP: CNT: CMC: SBR = 94: 1.5: 0.5: 1.5: 2.5. The raw materials are mixed and coated to obtain a negative electrode sheet.
[0106] Comparative Example 4
[0107] The mass ratio of the positive electrode layer is NCM811:SP:PVDF:CNT=96:1.5:2:0.5. The above raw materials are mixed and coated to obtain a positive electrode layer. Perfluorobutyltetrahydrofuran:CMS carbon molecular sieve=1:3 (mass ratio), mixed and evenly coated on the surface of the positive electrode layer, with a thickness of 15μm and a porosity of 25%. The mass ratio of the composite structure formed by perfluorobutyltetrahydrofuran and CMS carbon molecular sieve to the positive electrode active material in the composite positive electrode sheet is 0.1%. Thus, the composite positive electrode sheet G of Comparative Example 4 is obtained, and the composite positive electrode sheet G includes a surface functional layer containing a composite structure on the outermost surface of the positive electrode layer.
[0108] The negative electrode sheet is a graphite negative electrode, and the mass ratio of each component of the negative electrode is graphite: SP: CNT: CMC: SBR = 94: 1.5: 0.5: 1.5: 2.5. The raw materials are mixed and coated to obtain a negative electrode sheet.
[0109] The raw materials used are as follows:
[0110] NCM811 is a ternary positive electrode active material obtained by mixing nickel, cobalt and manganese in a ratio of 0.8:0.1:0.1, purchased from Ningbo Rongbai New Energy Technology Co., Ltd., trade name: nickel cobalt manganese oxide;
[0111] SP is a conductive carbon black purchased from Termeco, Switzerland, trade name: Super P Li;
[0112] PVDF is polyvinylidene fluoride purchased from Solvay, Belgium, trade name: PVDF 5130;
[0113] CNT is carbon nanotube purchased from Shanghai Haiyi Science and Trade Co., Ltd., trade name: single-walled carbon nanotube;
[0114] Perfluoro-n-butyltetrahydrofuran was purchased from Wuhan Kemik Biopharmaceutical Technology Co., Ltd., trade name: Perfluoro-n-butyltetrahydrofuran;
[0115] CMS molecular sieve was purchased from Iwatani Industry Co., Ltd., Japan, trade name: carbon molecular sieve;
[0116] CMC is carboxymethyl cellulose purchased from Nippon Paper Industries, Ltd., trade name: sodium carboxymethyl cellulose;
[0117] SBR is styrene butadiene rubber purchased from Zeon Co., Ltd., trade name: styrene butadiene rubber;
[0118] <Performance Evaluation>
[0119] A mixed solution of 1 mol / L LiPF6 (the solvent is ethylene carbonate and propylene carbonate, with a volume ratio of 3:7) is used as the electrolyte. Soft-pack batteries with a capacity of no more than 2Ah are assembled in an argon glove box. At an ambient temperature of 25°C, they are subjected to a hot box test with a heating rate of 5°C / min, from ambient temperature to 130°C or a specified temperature (such as 150°C), and the heating is stopped after maintaining for 30 minutes. They are observed at the experimental ambient temperature for 1 hour. If they fail, the experiment ends.
[0120] The test results are shown in Table 1.
[0121] Table 1
[0122] Hot box test Example 1 No fire or explosion at 150℃ Example 2 No fire or explosion at 155℃ Example 3 No fire or explosion at 160℃ Example 4 No fire or explosion at 155℃ Comparative Example 1 No fire or explosion at 130℃ (i.e., fire or explosion at over 130℃) Comparative Example 2 No fire or explosion at 130℃ Comparative Example 3 133℃ No fire or explosion Comparative Example 4 No fire or explosion at 135℃
[0123] It can be seen from the results of the above embodiments and comparative examples that by adopting the composite structure of the present invention in the positive electrode sheet, the self-heating reaction caused by the oxidizing gas and reducing gas generated in the lithium battery can be blocked, thereby suppressing the self-heating temperature increase of the battery under abuse conditions, reducing the amount of heat released, and reducing the probability of thermal runaway.
[0124] Therefore, by using a composite molecular sieve with a high oxygen capture / adsorption capacity, the active oxygen components generated by the positive electrode can be captured, and it can also isolate the positive and negative electrode sheets to prevent short circuits.
[0125] It should be noted that, although the technical solution of the present invention is introduced with specific examples, those skilled in the art will appreciate that the present invention should not be limited thereto.
[0126] The embodiments of the present invention have been described above, and the above description is exemplary, not exhaustive, and is not limited to the disclosed embodiments. Many modifications and variations will be apparent to those of ordinary skill in the art without departing from the scope and spirit of the described embodiments. The selection of terms used herein is intended to best explain the principles of the embodiments, practical applications, or technical improvements in the market, or to enable other persons of ordinary skill in the art to understand the embodiments disclosed herein.
Claims
1. A composite positive electrode sheet, comprising at least a positive electrode sheet layer, in, The positive electrode layer includes a composite structure uniformly distributed in the positive electrode active material, The composite structure is formed by loading molecules of an oxygen capture agent, which is liquid at room temperature, within the molecular sieve. 2 . The composite positive electrode sheet according to claim 1 , wherein the composite structure accounts for 0.5% to 5% of the mass of the positive electrode active material in the composite positive electrode sheet.
3. A composite positive electrode sheet, comprising at least a positive electrode sheet layer and a surface functional layer on the outermost surface of the positive electrode sheet layer, in, The surface functional layer at least includes a composite structure, The composite structure is formed by loading molecules of an oxygen capture agent, which is liquid at room temperature, within the molecular sieve. 4 . The composite positive electrode sheet according to claim 3 , wherein the composite structure accounts for 0.5% to 5% of the mass of the positive electrode active material in the composite positive electrode sheet. 5 . The composite positive electrode sheet according to claim 3 , wherein the thickness of the surface functional layer is 0.5 to 10 μm, preferably 1 to 5 μm, and the porosity of the surface functional layer is 10% to 40%.
6. The composite positive electrode sheet according to any one of claims 1 to 5, wherein the mass ratio of the oxygen capture agent to the molecular sieve is oxygen capture agent: molecular sieve = 1:30 to 1:1, preferably oxygen capture agent: molecular sieve = 1:9 to 1:1.
5.
7. The composite positive electrode sheet according to any one of claims 1 to 6, wherein the oxygen capture agent is selected from fluorine-containing carbon compounds, preferably at least one selected from perfluoro-n-butyltetrahydrofuran, perfluoro tertiary amine compounds, Freon E4, and perfluorodecalin compounds.
8. The composite positive electrode sheet according to any one of claims 1 to 7, wherein the molecular sieve is at least one selected from carbon molecular sieve, titanium silicon molecular sieve, silicon aluminum molecular sieve, and phosphorus aluminum molecular sieve, preferably at least one selected from CMS220 carbon molecular sieve, TS-1 titanium silicon molecular sieve, 3A molecular sieve silicon aluminum, and SAPO34 phosphorus aluminum molecular sieve. 9 . The composite positive electrode sheet according to claim 1 , wherein the pore size of the molecular sieve is 0.2 nm to 2 nm. 10 . The composite positive electrode sheet according to claim 3 , wherein the content of the molecular sieve is 40% to 90% relative to the total mass of the composite structure. 11 . The composite positive electrode sheet according to claim 3 , wherein the surface functional layer further comprises a binder, and the binder is at least one selected from polyacrylate, polyvinylidene fluoride and its derivatives, polyether, polyurethane, and polyamide.
12. The composite positive electrode sheet according to any one of claims 1 to 11, wherein the composite positive electrode sheet further comprises a solid electrolyte layer, wherein the solid electrolyte layer comprises an inorganic, organic or composite solid electrolyte, The inorganic solid electrolyte is at least one selected from oxide solid electrolytes, halide solid electrolytes, and sulfide solid electrolytes; the organic solid electrolyte is at least one selected from polyvinylidene fluoride, polyacrylonitrile, and polyacrylate; and the composite solid electrolyte is a composite structure of the inorganic solid electrolyte and the organic solid electrolyte.
13. A method for preparing the composite positive electrode sheet according to claim 1, wherein the composite positive electrode sheet comprises at least a positive electrode sheet layer and a composite structure uniformly distributed in the positive electrode sheet layer, The preparation method comprises the step of mixing the molecular sieve and the oxygen capture agent to form a composite structure. 14 . The preparation method according to claim 13 , wherein the preparation method comprises the step of uniformly mixing the composite structure with a positive electrode active material, a conductive agent, a binder and a solvent to prepare a positive electrode slurry.
15. A method for preparing a composite positive electrode sheet according to claim 3, wherein the composite positive electrode sheet comprises at least a positive electrode sheet layer and a surface functional layer on the surface of the positive electrode sheet layer, wherein the surface functional layer comprises a composite structure, The preparation method comprises the step of mixing the molecular sieve and the oxygen capture agent to form a composite structure. 16 . The preparation method according to claim 15 , wherein the preparation method comprises the step of coating the composite structure on the surface of a positive electrode layer to form the surface functional layer. 17 . The preparation method according to claim 13 , wherein the preparation method further comprises the step of forming a solid electrolyte layer in the composite positive electrode sheet using an inorganic, organic or composite solid electrolyte.
18. A diaphragm-free lithium battery, comprising at least the composite positive electrode sheet according to any one of claims 1 to 12 or the composite positive electrode sheet obtained by the preparation method according to any one of claims 13 to 17, and a composite negative electrode sheet.
19. A lithium battery, comprising at least the composite positive electrode sheet according to any one of claims 1 to 12 or the composite positive electrode sheet obtained by the preparation method according to any one of claims 13 to 17, and a composite negative electrode sheet.
20. The lithium battery according to claim 18 or 19, wherein: The composite negative electrode sheet at least comprises a negative electrode sheet layer, and optionally a solid electrolyte layer on the outermost surface of the negative electrode sheet layer. The negative electrode layer at least includes a negative electrode active material, a conductive agent and a binder, and the negative electrode active material is at least one selected from lithium metal, graphite or silicon-based negative electrode active materials.
21. The lithium battery according to claim 20, wherein the negative electrode layer further comprises a porous material, the pore size of the porous material is 0.3 nm to 1 nm, preferably 5A zeolite, The content of the porous material is 0.1% to 5% relative to the total mass of the negative electrode layer.
22. The lithium battery according to claim 20, wherein the solid electrolyte layer has a thickness of 5 μm to 20 μm and a porosity of 5% to 30%, The solid electrolyte layer comprises an inorganic, organic or composite solid electrolyte; The inorganic solid electrolyte is at least one selected from oxide solid electrolytes, halide solid electrolytes, and sulfide solid electrolytes; the organic solid electrolyte is at least one selected from polyvinylidene fluoride, polyacrylonitrile, and polyacrylate; and the composite solid electrolyte is a composite electrolyte of the inorganic solid electrolyte and the organic solid electrolyte.
Citation Information
Cited By
Positive electrode material, preparation method of intermediate of positive electrode material and positive electrode material
CN120483281A
A method for preparing a cathode material and an intermediate thereof, and a cathode material
CN120483281B
Inorganic solid electrolyte membrane positive pole piece and energy storage battery
CN121215682A
An inorganic solid electrolyte membrane positive electrode and energy storage battery
CN121215682B